THE POSITION OF THE WORKERS' OR LABORERS' SEVERANCE PAY AND OTHER RIGHTS IN THE BANKRUPTCY OF A COMPANY - Sonhaji Sonhaji (Diponegoro Law Review, 2018)
Bankruptcy shall mean general confiscation of all assets of a debtor who could no longer afford to pay the debts that are due and could be billed. In Indonesia, bankruptcy is already known before 1945. Bankruptcy is Commercial Court ruling which put all assets of a debtor in a public attachment status thereafter the appointed curator could manage and liquidate the assets of the bankrupt debtor (bankruptcy properties) which would be sold and distributed to all creditors based on their respective levels of entitlement including the wages owed and other rights (Severance pay, gratuity and other compensation benefits). Problems would rise if the company hiring the laborers is declared bankrupt by the Commercial Court. In such circumstances, wage repayments or remunerations to the laborers became an interesting topic to be studied. The company and the government are responsible upon the fulfillment of the laborers' wage rights. In case that responsibility is not fulfilled, then there had been a violation of the rights of the laborers' welfare and violations and blasphemy of human rights. In reality, the laborers' wages sometimes are not paid by the company where they worked because it had bankrupt and is unable to pay, because the company did not want to pay even though there is a decision from the Industrial Relations Court which required the employer (company) to pay the wages or the severance pays.